Using the Benthic Macroinvertebrates Species Diversity Index to Determine the Water Quality of Antirogo River, Jember Regency - Wimbaningrum, Retno; Utami, Eva Tyas; Agustina, Rizka; Setiawan, Rendy (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
The Antirogo river, as one of the rivers across the Jember regency, East Java, plays an important role and is used for various activities such as agriculture, domestic, and industrial activities. These anthropogenic activities could affect the water quality of the river and the biota within. A group of river biota affected by anthropogenic activities is the benthic macroinvertebrates. Benthic macroinvertebrates can be used as bioindicators of river water quality. This study aimed to assess the water quality of the Antirogo River using the Shannon Wiener species diversity index (H') based on benthic macroinvertebrate data. Benthic macroinvertebrate sampling was conducted using a Surber net at three research stations. This research found 1703 individuals of benthic macroinvertebrates, which were classified into 16 families, 10 orders, and five classes. The most abundant family was the Heptageniidae, while the least abundant was the Simuliidae. The benthic macroinvertebrates' diversity index (H’) value was 1.67, with the evenness index (E) value at 0.60. Based on the diversity index (H’) value, the water quality in this river was lightly polluted with pollutants that can be in the form of solid materials and toxic compounds.